Edible flowers as sources of bioactive compounds: Determination of phenolic extraction conditions - Yasar, Bahar; Kutlu, Gozde; Tornuk, Fatih (ELSEVIER, 2022)
Edible flowers (EFs), besides their traditional use, have been popularizing and taking increasing attention in food fashion in many countries. In this study, the optimum extraction conditions of crude phenolics from 3 EFs (jasmine (Jasminum officinale), mallow (Malva sylvestris) and cowslip (Primula veris)) were determined using response surface methodology (RSM). Extraction temperature (X1, 45-75 degrees C) and time (X2, 25-50 min) were selected as independent variables for maximization of the responses, namely extraction yield and total phenolic content (TPC). A 20:80 ratio of ethanol:water were used as a solvent. The predicted extraction conditions for the maximum yield were 75 degrees C, 50 min; 74.40 degrees C, 26.39 min and 75 degrees C, 25 min for jasmine (29.79%), mallow (27.30%) and cowslip (15.78%), respectively. Furthermore, the optimal conditions for the highest TPC were 61.43 degrees C for 50 min for jasmine (50.6811 mg GAE/g), 67.94 degrees C for 41 min for mallow (91.5834 mg GAE/g), and 61.41 degrees C for 49.98 min for cowslip (86.8096 mg GAE/g). Under the optimized conditions, TPC values, total flavonoid contents (TFC), antioxidant activities (DPPH, CUPRAC and FRAP) and phenolic acid profiles were also analyzed. In line with the findings, TPC values of jasmine, mallow and cowslip were 49.50 mg GAE/g, 90.20 mg GAE/g and 86.33 mg GAE/g, respectively, whereas jasmine extract had the highest TPC (16.56 mg CAE/g), followed by mallow (13.52 mg CAE/g) and cowslip (9.25 mg CAE/g). Based on the antioxidant activity findings, jasmine showed the best antioxidant activity among the EFs. The most abundant phenolic compounds in jasmine, mallow and cowslip were protocatechuic acid (1086.00 mu g/g), gallic acid (924.50 mu g/g), and rutin (269 mu g/g), respectively. In conclusion, the results confirmed that the selected EFs were good sources of natural antioxidants, which reveals their potential in food and pharmaceutical applications, thereby their commercial cultivation could be enhanced greater.
Keywords: Edible flowers; Extraction; Phenolic compound; Response surface methodology; Optimization; ANTIOXIDANT ACTIVITIES; HEALTH; L.; Food Science & Technology